Effects of ICT and media information on collective resilience after disasters – from a virtual crowd to a psychological crowd – Part 1 - ICT and media information and collective resilience in an emergency situation - John W. Cheng; Hitoshi Mitomo (International Telecommunications Society (ITS), 2016)
This paper is the first part of a two-part study that aims to examine the relationship between collective resilience and ICT and media information. Previous studies find that in disaster and emergency situations, most people are capable to remain coherent and to offer mutual help. Referred as collective resilience, this kind of collective behaviours has become an essential element in disaster resilience development. However, despite many studies show that ICT and media information can also motivate people in disasters, currently there are few studies that connect collective resilience with ICT and media information. This paper focuses on the relationship between collective resilience and ICT and media information in an emergency situation using uses the 2011 Great East Japan Earthquake as a case study. Specifically, it focuses on the tens of thousands of commuters who were stranded at the train stations for long hours because of the earthquake. Using a cluster analysis of data collected from an original questionnaire survey in Japan, we found that information from different media sources can contribute to people's collective resilience behaviours. In particular, under the external threats posed by the disaster, people who were better informed were more likely to be associated with others, and also to give and receive help.
Keywords: 330